2020
DOI: 10.1038/s41598-019-57368-w
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory macrophages coupled with glycolysis remodel adipose vasculature by producing platelet-derived growth factor-B in obesity

Abstract: Adipose tissue macrophages (ATMs) play a central role in tissue remodeling and homeostasis. However, whether ATMs promote adipose angiogenesis in obesity remains unclear. We examined the impact of ATMs deletion on adipose angiogenesis and tissue expansion in the epididymal white adipose tissue (eWAT) of high-fat diet (HFD)-fed mice by using liposome-encapsulated clodronate. We further elucidated the induction mechanisms of platelet-derived growth factor (PDGF)-B in macrophages in response to obesity-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…On the other hand, obesity-damaged AdECs could directly activate endothelial TLR-MyD88 signalling to drive M1 macrophages accumulation through production of GM-CSF, which is well known for promoting monocyte differentiation towards M1 pro-inflammatory macrophages [ 25 ]. Moreover, ATMs could regulate the formation of AdECs by producing po-angiogenic factors, such as the platelet-derived growth factor-B (PDGF-B) [ 26 ]. These findings suggest that AdECs harbour immunosuppressive feedback mechanisms that are triggered as a result of macrophage activation.…”
Section: Adecs Signalling Network Within Adipose Stromal Cellsmentioning
confidence: 99%
“…On the other hand, obesity-damaged AdECs could directly activate endothelial TLR-MyD88 signalling to drive M1 macrophages accumulation through production of GM-CSF, which is well known for promoting monocyte differentiation towards M1 pro-inflammatory macrophages [ 25 ]. Moreover, ATMs could regulate the formation of AdECs by producing po-angiogenic factors, such as the platelet-derived growth factor-B (PDGF-B) [ 26 ]. These findings suggest that AdECs harbour immunosuppressive feedback mechanisms that are triggered as a result of macrophage activation.…”
Section: Adecs Signalling Network Within Adipose Stromal Cellsmentioning
confidence: 99%
“…Additionally, glycolysis/gluconeogenesis pathways play an essential role in the process of carbohydrate metabolism in various tissues of the body. The disorder of this pathway can cause the occurrence of human myopathy and is closely associated with function of adipose tissue macrophages (ATMs) in a high–fat diet–induced model of mice for responding to cellular insulin resistance [ 42 , 43 ]. The Gene Expression Omnibus (GEO) database of humans from non-insulin dependent diabetes mellitus (NIDDM) and obesity found that the biosynthesis of amino acids and notch signaling pathway were down regulated in adipose tissues [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of HIF-1 (via VHL deletion) elevates the glycolytic enzyme pyru-vate kinase M2, which in turn downregulates the IL-33-ST2 pathway, thus directly impacting ILC-2 maturation [317]. Finally, in obese mice, it was recently demonstrated that palmitate upregulates ATM glycolysis and HIF-1 activation and induces IL-1β in macrophages [318]. Thus, enhanced glycolysis and HIF-1α activation in ATM could be partially driving the low-grade inflammation in obesity.…”
Section: Oxygen Availability Hifs and Immune Cells In Obesitymentioning
confidence: 99%
“…Fewer studies addressed the role of HIFs in myeloid cell populations (LysMCre) in the context of diet-induced obesity, again with contrasting results. Myeloid cell-specific HIF-1 deletion protects against adipose tissue inflammation and reduces macrophage crown-like structure formation [318,322]. However the role in glucose and insulin tolerance is controversial, with one study showing that myeloid HIF-1 deletion protected from the development of systemic insulin resistance in obese mice [322], whereas the second study showed no effect [318].…”
Section: Oxygen Availability Hifs and Immune Cells In Obesitymentioning
confidence: 99%
See 1 more Smart Citation